How far do Canadians need to travel to access cash? - Heng Chen; Daneal O'Habib; Hong Yu Xiao (Bank of Canada, 2023)
This paper develops a travel-based metric to measure Canadians' access to cash from automated banking machines (ABMs) and financial institution branches. Our findings indicate that the average distance Canadians need to travel to reach the nearest ABM is 2.0 km, while the average distance to the nearest branch is 4.5 km. Moreover, more than 90% of Canadians live within 5 km of an ABM, and 84% live within 5 km of a branch. The total number of ABMs in Canada increased by 3.7% between 2019 and 2022, and our results show that, overall, access to cash remained stable in that period. However, the total number of branches decreased by 5.2%. The decline in branch coverage is concentrated in rural areas at 7.2%. This may increase the challenge of accessing cash in these regions. Rural Canadians already have less access to cash: they need to drive an average distance of 4.0 km to the nearest ABM and 9.6 km to the nearest branch, each distance twice the national average.
Keywords: G21; J15; R51; 330; Financial services; Regional economic developments